KEWENANGAN KPPU DALAM MELAKUKAN PENGAWASAN BISNIS ONLINE DI INDONESIA - Sayyid Hasyeem Thorieq (Peneliti.net, 2023)
This study aims to analyze the authority of the Indonesian Competition Commission (KPPU) in supervising online businesses in Indonesia. Online businesses have experienced rapid growth in recent years and have become an integral part of Indonesia's digital economy. However, the growth of online businesses also presents new challenges in terms of oversight and regulation to ensure fair competition and adequate consumer protection. The research methodology employed in this study is literature review and analysis of legal documents related to the authority of the KPPU in supervising online businesses. The analysis reveals that the KPPU possesses sufficient authority to carry out supervision over online businesses. The KPPU can investigate allegations of unfair competition practices, such as cartels or abuses of dominant positions, conducted by online business operators. However, the KPPU faces several challenges in carrying out supervision of online businesses. These challenges include the complexity and rapidly changing nature of online businesses, the lack of adequate human resources and technology, as well as coordination between the KPPU and other relevant institutions in addressing violations in the online business sector. This study provides recommendations to strengthen the authority of the KPPU in supervising online businesses. These recommendations include enhancing cooperation between the KPPU and other relevant institutions, developing the expertise and capacity of KPPU staff in overseeing the online business sector, as well as improving the utilization of technology and data analysis to detect and address violations. This research is expected to contribute to understanding the authority of the KPPU in supervising online businesses in Indonesia and provide insights for improving the existing oversight system.